Tax morale and compliance behavior: First evidence on a causal link - Martin Halla (Institute for the Study of Labor (IZA), 2010)
Recent literature on tax evasion emphasizes the importance of moral considerations to explain compliance behavior. As a consequence scholars aim to identify factors that shape this so-called tax morale. However, the causal link between tax morale and actual compliance behavior is not established yet. Exploiting exogenous variation in tax morale - given by the inherited part of tax morale of American-born from their ancestors' country of origin - our instrumental variable analysis provides first evidence on a causal effect of tax morale on the size of the underground production.
Keywords: A13; O17; H26; Z13; C81; 330; Tax morale; tax evasion; tax compliance; underground production; Steuermoral; Steuerflucht; Schattenwirtschaft; USA